Corporate Criminal Liability under the United States Criminal Law - Toan, Trinh Quoc (VNU Journal of Science: Legal Studies; Vol 41 No 4, 2025)
This article examines and analyzes the issue of corporate criminal liability under the United States criminal law from the following perspectives: 1) the historical formation and development of the doctrine; 2) the scope and conditions for attributing criminal liability to corporations, including: the subjects bearing such liability; which specific acts of corporate members may be attributed to the corporation; the circumstances under which a member’s criminal act may be imputed to the corporation; and the major doctrines governing corporate criminal liability in the United States; 3) the sanctions applicable to corporations convicted of crimes.